Jovens e adultos no Ensino fundamental noturno público: os sentidos atribuídos aos estudos - Soares, Vera Lúcia da Silva (2014)
This current study aimed to reflect about the senses that students in 9th grade of a public night school Maceio City attributed to studies and their perspectives for the future. Specifically, the field research took place in a Municipal Public Education Network school, located in a neighborhood considered as upscale. The investigation turned to the young and adults who attended the Secondary School at the nocturnal period in this referred school. It is about a qualitative nature study, which achievement is the result of disquiets arisen in masters’ classes and readings about issues related to the senses given to studies by students today. Through the case study, we excel for data gathering, using the application of a questionnaire and semi-structured interviews. Led by educational area’s theorists, as Charlot (2005), Reis (2012a) and Sacristãn (1996), who contributed to the comprehension of the social function of nocturnal school, the sense of the meaning and relationship with the school knowledge, the data analysis was achieved from two categories of analysis, which are: the senses expressed by students in school life and schooling. In its conclusion, the study points out that the major evidence attributed to the senses given to studies by the students is in the relationship between process of schooling and social mobility. It was further observed that the perspectives regarding studies are great, and that, even facing dilemmas as to continue or not the studies, young and adults believe they can only have expectations to the future and changes in their personal lives from continuity in the process of schooling.